Application of the family-centered nursing theory in the education of children with hearing impairments: an analysis of the relationship between parental support and academic achievement - Pepy Saudia Ardani; Wiwik Utami; Agus Ari Afandi; Siti Patonah (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Children with special needs possess intellectual potential comparable to that of typically developing peers; however, they often face challenges related to communication, social adaptation, and learning that necessitate structured family and educational support. Within this context, family engagement plays a crucial role in fostering academic and psychosocial development, especially for children with hearing impairments who require inclusive learning environments. Purpose: to explore the application of the Family-Centered Nursing theory in the educational setting of children with hearing impairments, specifically analyzing the relationship between parental support and academic achievement. Method: A quantitative cross-sectional correlational design was employed involving 44 parents of children with hearing impairments enrolled at the Special School (SLB) in Bojonegoro City, Indonesia. Data was obtained using a validated 22-item parental support questionnaire (Cronbach’s alpha = 0.929) and students’ report card scores as indicators of academic performance. Statistical analysis was conducted using the Spearman’s rho correlation test. Results: The findings demonstrated a strong and positive correlation between parental support and academic achievement (Spearman’s rho = 0.870, p < 0.05). Higher levels of emotional, informational, appraisal, and instrumental support were significantly associated with better academic performance, with emotional support emerging as the most influential factor enhancing motivation and learning engagement among children. Conclusion: The study highlights the theoretical and practical significance of the Family-Centered Nursing approach beyond healthcare contexts, emphasizing its relevance in promoting inclusive education for children with disabilities. The results underscore the need for family-based educational interventions and interdisciplinary collaboration among nurses, educators, and policymakers to strengthen parental involvement and improve academic outcomes for children with hearing impairments.